2020
DOI: 10.1002/pssr.202000083
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of CsPbBr3 Nanocrystal Light‐Emitting Diodes via Atomic Layer Deposition

Abstract: Perovskite nanocrystal (PNC) suffers from solution corrosion and water/oxygen oxidation when used in light‐emitting diodes (LEDs). Atomic layer deposition (ALD) is applied to introduce Al2O3 infilling and interface engineering for the CsPbBr3 nanocrystal emission layers, and the inorganic electron transport layer‐based CsPbBr3–ZnMgO LED device is fabricated. The introduction of Al2O3 ALD layers significantly improves the tolerance of CsPbBr3 PNC thin films to polar solvents ethanol of ZnMgO during spin coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…As a result, QD films have a strong resistance to external solvents, and PR can be directly coated on top of the QD. Similar strategies have been attempted in perovskite materials to achieve solvent orthogonality during device fabrication, but patterning of nanocrystals has been developed for the first time in the present work. In addition to depositing layers of ZnO by a few cycles of ALD, exposing the DEZ for a few seconds is sufficient to provide solvent resistance of the QD film.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, QD films have a strong resistance to external solvents, and PR can be directly coated on top of the QD. Similar strategies have been attempted in perovskite materials to achieve solvent orthogonality during device fabrication, but patterning of nanocrystals has been developed for the first time in the present work. In addition to depositing layers of ZnO by a few cycles of ALD, exposing the DEZ for a few seconds is sufficient to provide solvent resistance of the QD film.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some works implied that the photoluminescence of QDs after ALD became inferior to those pristine ones 104 . The contradictory conclusion may attribute to the loss of surface ligands 88 or the replacement of QDs cations by metal precursor 69 .…”
Section: (Iii) and (Iv)mentioning
confidence: 99%
“…The introduction of Al 2 O 3 /ZnO ALD layers significantly improves the tolerance of CsPbBr 3 PNC thin films to polar solvents (ethanol) during deposition of electron transport layer and increases the operation lifetime. 48,49 However, in spite of providing conformal overcoating, protection against environmental factors, and improving carrier transport properties, the metal oxide deposition process greatly quenches the photoluminescence of perovskite NCs, 45 with partial decomposition into PbI 2 observed in some cases of MAPbI 3 . 43 Lowering the metal oxide deposition temperature and changing the metal/oxygen precursors have been explored to circumvent this detrimental effect.…”
mentioning
confidence: 99%
“…Among a number of surface stabilization strategies, atomic layer deposition (ALD) of metal oxides has received continuous attention. It has been demonstrated that alumina encapsulation improves long-term stability and retains the integrity of perovskites during device fabrication. , The earliest applications included use of ALD Al 2 O 3 as an overlayer on CH 3 NH 3 PbI 3 sensitized solar cells which could act as a barrier to protect the easily dissolvable perovskite sensitizer. , These were followed by more elaborate approaches where metal oxides were applied throughout perovskite solar cell (PSC) structures as well as for outside encapsulation. Lately, ALD has been employed to encapsulate fully inorganic perovskites and solution-processed nanocrystals (PNCs) that are developed for LED and laser applications. However, in spite of being effective for external surface protection and improving carrier transport properties, the metal oxide ALD procedure often diminishes optical properties of the perovskite materials, especially solution-processed PNCs, to a significant extent. More specifically, degradation is attributed to the detrimental reaction of Al precursor with the surface atoms of the material, impeding use of ALD-based encapsulation for applications that require high photoluminescence (PL) quantum yield of the active material. ,, We highlight how a recently established and developed gas-phase ALD technique enables precise control of the surface reactions and leads to the investigation of the precise atomic interactions taking place on the perovskites’ surfaces during aluminum oxide deposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation